STUDENTS’ ABILITIES IN WRITING DESCRIPTIVE TEXT AT GRADE SEVENTH STUDENTS OF SMP DAR AL-FALAH IN TANJUNGBALAI - deasy yunita siregar (VISION, 2022)
Writing is the most important skill that we should consider because the student must know how to write a text grammatically and correctly. Descriptive text is a piece of text that describes a place, person, or thing. This research was aimed to analysis of students’ difficulties in writing descriptive text at grade seventh students of SMP Daar Al-Falah in Tanjngbalai.. In this research, researcher uses the quantitative description data. The most problems faced by the students were grammar and organization with a total mean 75, 18. And based on the result of this research, there are 16 students who able in writing descriptive text by percentage 73%. And there are 6 students who unable in writing descriptive text by percentage 27, 27%. This suggested that teacher cold more improve their skill in the descriptive text in an interesting way or strategy. Keywords: Writing, Descriptive text,.